A 1MW Magnetron Radar Transmitter Upgrade Using Modular Line-type Solid-state Pulse Modulator - Rondani, B.; Pomilio, J. A.; Levy, R. R.; Lamarche, J. C. (Eletrônica de Potência, 2006)
This paper describes the upgrade of Atlas tracking radar system transmitter at Alcantara Launch Center (CLA), Maranhão, Brazil. The original transmitter installed in the 1980’s was equipped with a conventional hard-tube pulse modulator to excite a 1MW C-band magnetron. In order to extend overall system lifetime, improve reliability and introduce new monitoring and command functions the original tubetype modulator and control system was substituted by a modular line-type solid-state modulator and a digital control system.